2015
DOI: 10.15171/ijpni.2015.02
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of natural ingredients from the Mesoamerican biodiversity for the phytocosmetic industry

Abstract: IntroductionMesoamerica is a cultural and historical region were several important civilizations developed, such as Toltec, Zapotec, Maya and Aztec. Guatemala is a diverse country, pluricultural and multilingual, with a profoundly syncretic culture as a heritage of Maya and Spanish cultures. It is a region of high diversity, which complement the biological richness with a profound value for this local biodiversity by its inhabitants with an integral vision, including diverse applications such as flavors, aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Indeed, the study by Silva and colleagues (2012) [26] successfully demonstrated that the ethanolic extract of L. guatemalensis was effective against hyperalgesia. This was in addition to the antimicrobial, anticancer and antioxidant activities that have been reported for the extracts and essential oil of L. guatemalensis [50,58,[140][141][142][143].…”
Section: Litsea Guatemalensis Mezmentioning
confidence: 61%
“…Indeed, the study by Silva and colleagues (2012) [26] successfully demonstrated that the ethanolic extract of L. guatemalensis was effective against hyperalgesia. This was in addition to the antimicrobial, anticancer and antioxidant activities that have been reported for the extracts and essential oil of L. guatemalensis [50,58,[140][141][142][143].…”
Section: Litsea Guatemalensis Mezmentioning
confidence: 61%
“…Evolution in fields like ethnobotany, pharmacognosy, phytochemistry, analytical chemistry, efficacy and toxicology and even new available techniques and technologies on prospection, identification of plants, extraction and scale up processes, as well as new formulation possibilities, just to mention a few, guarantee a propitious moment for phytocosmetics from a technical and scientific point of view. 2,3,8,9 Another component not completely explored is the study conducted from traditional knowledge. Despite any controversy, many of the ancient pharmacopoeias were written based on the traditional knowledge about the use and known properties of plants all around the world.…”
mentioning
confidence: 99%